A synergistic blend of dietary organic acids, monoglycerides and phytobiotics enhance growth performance, intestinal mucosal height, and anti-viral immune gene expression in juvenile Barramundi (Lates calcarifer) - Charlene Goh; Susan Gibson-Kueh; David Bal; I.-Tung Chen; Waldo Nuez-Ortín; Jose A. Domingos; Xueyan Shen (Aquaculture Reports)
Barramundi or Asian seabass, Lates calcarifer, is an important food fish species in tropical aquaculture, but intensive farming is associated with increased susceptibility to various bacterial, viral, and parasitic diseases. Recent findings suggest that functional diets provide a broader advantage over the pathogen-specific protection of vaccines by improving growth performance, gut health, and immunity in teleosts. In this study, we conducted a six-week feeding trial in juvenile L. calcarifer (50.1 ± 0.0 g) whereby growth and production performance on a diet containing 0.5 % of a synergistic blend of organic acids, monoglycerides esters of organic acids and phytobiotics (OMGP) was compared with a control diet (CTRL), using quadruplicate 500 L tanks with 30 fish per tank. At the end of six weeks, juveniles were injected with Poly(I:C) to evaluate if the OMGP blend feed additive stimulates anti-viral immune responses based on a comparative RNAseq study 24 hour (24 h) and 72 h post-challenge. Juveniles fed with the OMGP blend exhibited an 8 % higher average final body weight (147.5 ± 6.9 vs. 136.5 ± 4.6 g) and a 6 % higher overall final biomass (4087 ± 107 vs. 3855 ± 149 g) compared to CTRL group (P < 0.05). The addition of the OMGP blend resulted in significantly reduced fasting blood glucose levels, higher white blood cell counts and greater intestinal mucosal villi heights compared to fish fed CTRL diet. OMGP fed L. calcarifer exhibited an increased number and upregulation of differentially expressed genes associated with infectious disease related immune pathways, such as Toll-like receptor (TLR) and NOD-like (NLR) receptor signaling, and Chemokine signaling pathways. Incorporating organic acids, monoglyceride esters of organic acids and phytobiotics improved growth performance, increased intestinal mucosal villi heights, and modulate the anti-viral immune capacity of juvenile L. calcarifer.